STUDY ON EMPLOYEES’ PERCEPTION ON INTERNAL MARKETING STRATEGIES OF SEVERAL ROMANIAN COMPANIES - Luigi Dumitrescu; Iuliana Cetină; Alma Pentescu (European Scientific Journal, ESJ, 2014)
Concerned to increase their efficiency and effectiveness in an increasingly competitive environment and under the pressure of educated and demanding customers, the Romanian companies must adopt the internal marketing view in the relations with their employees. In this context, this paper puts forth the following three objectives: (1) to highlight the internal marketing’s importance in adopting customer orientation within Romanian companies; (2) to present the content of internal marketing; and (3) to highlight, trough a direct marketing research, the application of internal marketing strategies and tactics in the activity of large companies and small businesses operating on the Romanian market. The conclusions drawn from this research can be capitalized on applying the marketing view within these companies’ activity. This paper also shows, from the employees’ point of view, that there are some differences in applying internal marketing strategies and tactics within large companies and small businesses.